Formação de círculo de leitura e clube de leitura para o letramento literário na escola - Maria Guimarães Gomes Otoni (2023)
In this research, literary literacy activities were developed with students from the final years of Elementary School, the focus was on training literary readers through the creation of reading circles, with the aim of forming a literary reading club at school. The objective of this academic work was based on reading experiences lived by students and observed in previous years. Based on studies about reading literature teaching (CAVALCANTI, 2002; MOISÉS 2003; CANDIDO, 2004; PAULINO, COSSON, 2009; COMPAGNON, 2010; ZILBERMAN, 2011; ALMEIDA et al., 2012; BARTHES, 2013; DIONÍSIO, 2014; BRANCO, 2014; COSSON, 2020, 2021a, 2021b; PAULINO, 2021; TODOROV, 2021; VARGAS 2021), on intervention research (DAMIANI, 2013) and on the guidelines about language practices present in the official document Base Nacional Comum Curricular (BNCC): Educação Infantil e Ensino Fundamental (BRASIL, 2018), an intervention proposal of qualitative-propositive nature was elaborated, in order to be developed with students from the 9th grade of elementary school.enrolled at Escola Estadual Nilo Maurício Trindade Figueiredo,placed at Lagoa Santa town, in the state of Minas Gerais.The students participated of reading sharing practices, reception of literary works, the tales “Venha ver o pôr do sol” of Lygia Fagundes Telles(2007) and “Negrinha” of Monteiro Lobato(2009), formation of reading circles, development of group activities and motivation for the development of literary reading culture. The research on literary literacy carried out, moves towards to the formation of a reading-enjoyer, who is able to relate his/her living with the literary art and from there reflects on his/her attitudes and pondering judgments and values in their social relationships. In the end, a reading club with the students, who participated in the research, was created: during a talk circle among six participants of the research, the students expressed their interest or not in founding the club. During the talk circle, two opposing students were convinced by their colleagues to participate. In the end, the club was formed with three students who were present and two more absent, who had already expressed interest and passed the information to the colleagues. This practice became seed with the promise of good fruits.